Implementasi Kurikulum Merdeka Di Smp Negeri 11 Surabaya - Komaria, Nurul; Hariyoko, Yusuf (Faculty of Social and Political Science, 2023)
Education in Indonesia has experienced several curriculum changes. The curriculum is used as a tool to achieve educational goals. The curriculum plays an important role in education by preparing learning plans which include subjects, teaching methods, and teaching materials prepared for students' learning process in acquiring knowledge. Basically, the Independent Curriculum requires educational units in schools to provide full support to students, not only in learning methods but also by providing adequate resources. This research aims to determine the implementation of the Independent Curriculum. The research method used is descriptive qualitative. The data used in this research is primary data obtained from direct observation in the field, while secondary data was collected from reference source for journal articles. The research results show that the Independent Curriculum policy has been determined clearly and in detail by policy makers. However, in its implementation, there are resource challenges in implementing the Independent Curriculum policy at SMP Negeri 11 Surabaya. Policy implementers have the responsibility to provide the necessary resources to ensure the smooth implementation of established policies. In this way, policy implementation can be carried out well.